Tumoral CD10 expression correlates with high-grade histology and increases risk of recurrence in patients with stage I lung adenocarcinoma. Issue 3 (September 2015) - Kadota, Kyuichi; Buitrago, Daniel; Lee, Ming-Ching; Villena-Vargas, Jonathan; Sima, Camelia S.; Jones, David R.; Travis, William D.; Adusumilli, Prasad S.
Highlights Tumoral CD10 correlates with high-grade tumor histology. Tumoral CD10 is a predictor of recurrence in intermediate-grade tumors. CD10 stratifies patients with intermediate-grade tumors into two prognostic subgroups. CD10 helps select patients at high-risk of recurrence for post-surgery adjuvant therapy.